Nutrition of Florida Citrus Trees, Third Edition - Davie Mayeso Kadyampakeni; Kelly T. Morgan (EDIS, 2020)
This update to 2007's second edition adds information regarding nutrition of Florida citrus trees affected by huanglongbing (HLB), also known as citrus greening. Much of the guidance provided in this document on nutrients, application methods, leaf and soil sampling, and irrigation scheduling is also effective for trees affected by HLB. However, research conducted since the previous edition was published has established changes in many production practices, including nutrient rates, irrigation scheduling, soil pH management, and use of Citrus Under Protective Screen (CUPS). Changes to the second edition will appear at the beginning of chapters 2, 6, 8, 9, and 11. See also this topic page for links to individual chapters in HTML and PDF formats. This 115-page book was edited by Kelly T. Morgan and Davie M. Kadyampakeni, and published by the UF/IFAS Department of Soil and Water Sciences.